Characterizing honeybee cuticular hydrocarbons during foraging - Balbuena, María Sol (2019)
Honeybees (Apis mellifera) adjust their time and effort during foraging activity. Their metabolic rates together with body temperature rise while gathering profitable resources. These physiological changes may result in a differential cuticular profile, which in turn may bear communicational value. We evaluated if sucrose concentration of collected food affects the cuticular chemistry of honeybees during foraging. We trained bees to artificial feeders with high (2 M) and low (0.5 M) sucrose concentrations, and captured the active foragers for surface extraction of cuticular compounds. We sampled foragers just after feeding, before taking-off towards the hive, and upon landing at the hive entrance, before entering the hive. Through gas chromatography-mass spectrometry analysis of cuticular extracts, we identified and quantified 48 compounds, including cuticular hydrocarbons (CHCs) and volatiles associated with exocrine glands. We found that higher sucrose concentrations resulted in increased amounts of alkanes and alkenes in the surface extracts of foragers captured at the hive entrance, but not at the feeding site. Our results suggest that the differences that have been reported for CHCs in waggle-dancing honey bees can be already found once they return to the hive from profitable food sources.